The implementation of the Women, Peace and Security (WPS) agenda in the European Gendarmerie Forces - Malheiro, Luís (International journal of police science & management, 2024)
This investigation aims to study implementation of the Women, Peace and Security (WPS) agenda in the interventions of gendarmeries under the aegis of the European Gendarmerie Force (EGF), because two decades after its creation, there is evidence that the WPS is falling behind on its initial promise. Using a mixed strategy with a case study design, data were collected in 14 countries using structured interviews with 24 organisations linked to security in the European Union, including 6 linked to the EGF. After densifying the evolution of conflict, the window of opportunity that led to creation of the EGF and the implications of EGF’s current organisation not having structures dedicated exclusively to gender, suggestions obtained from the primary information were dissected. Integration of ideas in the literature with the results of this study suggest that the main obstacles to innovation for implementation of the WGS result from: (a) existing limitations in the institutions that make up the EGF; (b) lack of a plan to implement the WGS agenda; (c) lack of resources (materials and/or structures dedicated to gender); and (d) failure to incorporate a gender perspective into all planning dimensions.